Theoretical Explanations of the Development of Youth Hacking. - Kim, Jihoon; Leban, Lindsay; Lee, Yeungjeom (Crime & Delinquency, 2024)
Hacking, particularly among youth, is a relatively new form of deviance and its etiology is not well understood. Moreover, there is a lack of developmental approaches to understanding youth hacking, and the majority of studies on predictors of hacking have been cross-sectional. In light of this, we draw on prospective longitudinal data on a sample of Korean youth to explore theoretical predictors of youth hacking through a developmental lens. Cross-lagged dynamic panel models are employed to examine time-variant and time-invariant theoretical predictors of hacking. Results show that well-known criminological predictors are significantly associated with youth hacking, which implies the applicability of traditional criminological theories in online deviance. Limitations, suggestions for future research, and implications for practice are discussed.